Cytoprotection of the Gastric Mucosa and Eradication Therapy of Helicobacter Pylori Infection: Points of Conjugation - A. S. Trukhmanov; D. E. Rumyantseva; T. L. Lapina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present data on the main components of gastric mucosal protection and the possibilities of H. pylori eradication and cytoprotective pharmacotherapy for its restoration.Key points. The various components of the protection system correspond to the pre-epithelial, epithelial and post-epithelial levels in accordance with the structural organization of the gastric mucosa. Colonization of the gastric mucosa by H. pylori and the development of acute and chronic gastritis are possible due to a number of factors, including the form of the bacterium, the presence of virulence factors (CagA, VacA, OipA), and adhesion proteins (BabA, SabA). H. pylori has a negative effect on all levels of protection of the gastroduodenal mucosa, for example, it affects the secretion of mucins, disrupts the tight junction proteins functioning. Eradication of H. pylori infection eliminates its negative effects. An increase in the effectiveness of H. pylori eradication therapy is achieved by including rebamipide in therapy regimens. In the Russian Federation the eradication efficiency with the addition of rebamipide to treatment was 90.38 % compared with 81.68 % without rebamipide. The inclusion of rebamipide in the treatment regimen when prescribing standard triple therapy with bismuth tricalcium dicitrate allows achieving successful eradication rates of more than 95 %. The cytoprotective properties of rebamipide are due to an increase in the synthesis of endogenous prostaglandins, mucins containing O-glycans, and a decrease in oxidative stress and inflammation.Conclusion. Eradication of H. pylori infection helps restore the protective properties of the gastric mucosa. Rebamipide, when included in H. pylori eradication therapy regimens, increases its effectiveness. The cytoprotective effects of rebamipide make it possible to prescribe it for long-term treatment of post-eradication gastritis.